Pelatihan dan Pendampingan Cara Pembuatan Minuman Kesehatan Dari Bahan Alam Untuk Meningkatkan Imunitas di Kelurahan Kambo - Chitra Astari; Ervianingsih Ervianingsih; M. Zainal S; Eghy Andriani Achmad; Herika Hamka; Sulistiyaningsi Sulistiyaningsi; Mustafa Mustafa; L.M Almufakhir Idris (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2022)
Disinformation about diseases spread by viruses appears on a variety of topics, ranging from misinformation regarding the etiology, prevention and cure of viruses. The worst impact of this is the shift of people to ineffective and potentially life-threatening treatments, the emergence of public overreactions such as excessive purchases of certain medicinal products, causing soaring prices and scarcity of these medicinal products and in this situation many people become addicted to drugs. stress, panic and even fall ill. The purpose of this activity is to increase awareness, willingness and ability to live healthy for everyone so that they can realize the highest level of public health and is an active response to the Circular Letter of the Ministry of Health of the Republic of Indonesia Number: HK.02.02/IV.2243/2020 concerning Utilization of Traditional Medicines for Health Maintenance, Disease Prevention and Health Care, where people are encouraged to carry out health care independently (independent care) and properly through the use of medicinal plants as traditional medicines during Public Health Emergencies and/or National Disasters. It is hoped that this activity can increase public knowledge about how to maintain health and improve the immune system with traditional medicinal plants, optimally use yard land for traditional medicinal plants and be able to maintain and use them without having to buy and consume chemical drugs.